ANALISIS ELASTISITAS BATU BATA YANG DIBUAT DENGAN TEKNIK PEMANAS TENAGA SURYA MENGGUNAKAN REFLEKTOR CERMIN CEKUNG - Anda Yani; Muhammad Edisar; Antonius Surbakti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The research has been conducted to investigate the quality of some bricks. The quality of the bricks was tested after heating by solar energy using concave mirror reflector on their elastic properties. The quality of the bricks after being heated was compared with the bricks that were prepared by conventional way (by heating using fire). The elasticity properties were calculated from the time propagation of the seismic wave in the bricks. The results of the research showed that the elasticity of the bricks heated using solar energy for 80 hours was 50.623 (N/m²), and the lowest elasticity heated for 10 hours was 16.530 (N/m). While the elasticity of bricks heated using fire with the distance of 0.7 meters was 72.199 (N/m²) and the lowest elasticity of bricks with the distance from fire of 0.76 meter was 32.555 (N / m²). The results also showed that the quality of the bricks was better through direct burning using fire compared to the one prepared by solar energy.